Rett Syndrome and Fragile X Syndrome: Different Etiology With Common Molecular Dysfunctions - Bach, Snow; Shovlin, Stephen; Moriarty, Michael; Bardoni, Barbara; Tropea, Daniela (Frontiers in Cellular Neuroscience, 2021)
Rett syndrome (RTT) and Fragile X (FXS) are two monogenetic neurodevelopmental disorders with complex clinical presentations. RTT is caused by mutations in the Methyl-CpG binding protein 2 gene (MECP2) altering the function of its protein product MeCP2. MeCP2 modulates gene expression by binding methylated CpG dinucleotides, and by interacting with transcription factors. FXS is caused by the silencing of the FMR1 gene encoding the Fragile X Mental Retardation Protein (FMRP), a RNA binding protein involved in multiple steps of RNA metabolism, and modulating the translation of thousands of proteins including a large set of synaptic proteins. Despite differences in genetic aetiology, there are overlapping features in RTT and FXS, possibly due to interactions between MeCP2 and FMRP, and to the regulation of pathways resulting in dysregulation of common molecular signalling. Furthermore, basic physiological mechanisms are regulated by these proteins and might concur to the pathophysiology of both syndromes. Considering that RTT and FXS are disorders affecting brain development, and that most of the common targets of MeCP2 and FMRP are involved in brain activity, we discuss the mechanisms of synaptic function and plasticity altered in RTT and FXS, and we consider the similarities and the differences between these two disorders.